Does the Food Sovereignty Movement Exist in Negros? The BIND and ONOPRA Experiences - Sánchez, Benedicto Q. (Kasarinlan: Philippine Journal of Third World Studies, 2012)
While food sovereignty as a term is virtually absent in Negros Occidental development literature, the concept is not. The efforts to address hunger, unemployment, and underemployment during annual tiempos muertos also comprise a movement that seeks to resolve sugarcane monocultures in Negrense haciendas. Organic agriculture, on the other hand, was and is the means to diversify the provincial rural economy, restore the degraded environmental resource base, and attain food security among the perennially hungry food producers. The food sovereignty movement as such arose in Negros Occidental in the mid-1980s to address the near-famine proportions spawned by the crisis of the monoculture-based sugar industry. The emphasis on smallholder food producers, the concerted resistance to transnational companies’ promotion of genetic engineering to increase crop productivity, recognition of food security as a human right, the role of the state policy to protect and defend the right to seeds, indigenous knowledge systems, and the promotion of ecologically friendly farm technologies hew to the classical definitions of food sovereignty. The Negrense experience has put organic agriculture in its definition of “sustainable agriculture.” Moreover, the Negros food sovereignty movement sees subsistence agriculture and food security not as the be-all and end-all of organic agriculture but as the foundation to move beyond subsistence toward demand-driven organic crop production, including possible export to the international market.
Keywords: food sovereignty; food security; tiempo muerto; subsistence agriculture; organic agriculture; sugarcane monocultures; monopolies; value chain; demand-driven economy; agrobiodiversity